Pembinaan Profesionalisme Guru MI Berbasis Nilai-Nilai Profetik Melalui Pelatihan dan Pendampingan Penelitian Tindakan Kelas Terintegrasi - Tamsik Udin; Maman Rusman; Dwi Anita Alfiani (Dimasejati: Jurnal Pengabdian Kepada Masyarakat, 2024)
PROFESSİONAL DEVELOPMENT OF MI TEACHERS BASED ON PROPHETİC VALUES THROUGH INTEGRATED CLASSROOM ACTİON RESEARCH TRAİNİNG AND MENTORİNG. Classroom Action Research (PTK) produced by Madrasah Ibtidaiyah (MI) teachers currently tends to be subject-based, while 80% of learning in MI is thematic. In addition, the content of the PTK is less related to prophetic values in accordance with the MI Teacher profession.The objectives of this community service are (1) Providing professionalism coaching for MI teachers based on prophetic values about class action research (2) Improving writing skills to MI teachers about preparing class action research designs (3) Providing solutions to the obstacles faced by teachers in preparing class action research.The method used in this community service is the action research method. Action research is research that aims to see the impact of action and assess the actions taken so as to improve the quality of practice carried out.The results of this community service are (1) Professionalism development activities for teachers based on prophetic values through integrated class action research training in Madrasah Ibtidaiyah Cirebon City have been carried out through Focus Group Discussion (FGD) activities and PTK Making Assistance. (2) Teachers' understanding of Classroom Action Research has increased significantly as seen from the average pretest score of 45.65 and the average post-test score of 81.73. meaning that the training activities carried out have a positive impact on teacher understanding (3) The ability of teachers to design class action research is included in the good category with an average score of 75, which means that through this training and mentoring activity teachers are able to design and carry out class action research.